(untitled) (Research, Society and Development, 2024)
The aim of this work is to conduct a literature review on the benefits of orthodontic treatment in patients with reduced periodontium. As such, the methodology employed was a search of scientific articles in PubMed, Scopus, ScienceDirect and Cochrane from 2019 to 2024 with MeSH terms, DeCs and open terminology. In addition, eligibility criteria suitable for this study. Thus, a result of 876 was propitiated, of which 18 were chosen for this review, being mostly cohort studies, in addition to including finite element analysis, systematic reviews with meta-analysis, prospective cross-sectional studies, randomized clinical trial, literature review and a longitudinal study. In conclusion, orthodontic treatment allows for CAL gain and PPD reduction. In addition, dental alignment allows easy access to hygiene, thus altering the course of periodontal disease. In the case of gingival recession, the literature does not clearly explain the benefits that orthodontics can bring, a subject that remains open for future research.